THE IMPACT OF ANXIETY ON SPEAKING IN ADOLESCENT AND ADULT GROUPS OF ENGLISH LEARNERS - Gosiewska-Turek, Bogusława (Journal of Education Culture and Society, 2018)
Aim: The aim of this article is to investigate the interdependence between adolescent and adult students’ anxiety and their foreign language speaking achievements. It has been proved that there is no correlation between adolescent learners’ anxiety and their speaking attainments in a foreign language as well as that there is a weak correlation between adult students’ anxiety and their speaking achievements. Method: The author of the study employed quantitative research. Data was collected from anxiety questionnaires completed by the students and from achievement sheets filled in by the English teacher based on five-minute speeches performed by adolescent and adult students. Conclusion: According to the research results, there is no interdependence between adolescent students’ anxiety and their speaking attainments and the correlation between adult students’ anxiety and their speaking achievements is weak. Nevertheless, a number of other studies revealed the interdependence between students’ anxiety and their speaking attainments. Therefore, limitations of the study should be born in mind, and the results of the following study can be applied only to the subjects participating in the study. Hence, it is relevant to repeat the study with larger samples of subjects.